ETIKA HINDU DALAM CERITA TANTRI KAMANDAKA - Ni Luh Putu Trisdyani; Ida Bagus Putu Eka Suadnyana Eka Suadnyana (Jnanasidanta, 2019)
Satua Bali is one of Bali's kind of literature in its delivery using spoken language and in it contains the values of such a noble education : religious values , cultural values , ethics or moral values as well as values tatwa or philosophy. Satua Bali as one of the stories for the kids loaded with educational value , one of which is the story Kamandaka Tantri, Kamandaka Tantri story as one of the cultural product in containers using animal figures are expressed in the form of human behavior are full of messages religious so it needs to be developed and disseminated among the public in order to increase the sense of devotion presented to Ida Sang Hyang Wasa Widhi and contain educational value sublime.Keywords : Values, Education Hinduism, Stories, Tantri Kamandaka